Model Pembelajaran Berbasis Proyek (PJBL) Sebagai Implementasi Kurikulum Merdeka di TK Aba 25 Medan - Riani, Nova (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the implementation of the Project-Based Learning (PjBL) model as the implementation of the independent curriculum in Kindergarten Aba 25 Medan. This research uses the type of research and development (Research & Development). The data collection method is observation and documentation. Techniques in data analysis Techniques in data analysis used are qualitative descriptive. The development stage consists of planning, implementation, observation, and reflection stages. The results of the analysis show that in the first development stage when teachers implement the Project-Based Learning Model as the Implementation of the Independent Curriculum which is carried out reaches an average percentage of 83.33% with a very appropriate category while for child development during its implementation it reaches an overall average of 68.43% with a category that is still developing. The second development stage when teachers implemented the Project-Based Learning Model as the Implementation of the Independent Curriculum which was carried out reached an average percentage of 91.66% with the category being very appropriate, while for child development during its implementation it reached an overall average of 85.93% with the category of developing as expected